PENDAMPINGAN USAHA BAKSO GOYANG LIDAH UNTUK MENINGKATKAN DAYA SAING PRODUK - Ita Purnama; Nurfitrah; Nurul Hidayanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Micro, small, and medium enterprises (MSMEs) are the main businesses of the community in the economic activities in Indonesia, especially in the food industry. Meatballs are one of the typical foods of Indonesia that are very popular throughout the country. In Bima Regency, the goal of this service is to develop MSMEs in terms of product innovation and also increase the selling value of MSMEs. 'Baso Goyang Lidah' is one example of an MSME that requires assistance in product innovation. The methods used in community service activities are divided into three stages: the survey stage, the socialization of product variant development, and the maintenance and evaluation stage. This form of community service aims to develop and participate in assisting product innovation for 'Baso Goyang Lidah' MSMEs, so that it can increase the selling value and competitiveness of products that are not limited to the market.